2015
DOI: 10.4269/ajtmh.14-0652
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Travel-Related Severe Plasmodium vivax and Plasmodium falciparum Malaria in Individuals Hospitalized at a Tertiary Referral Center in Lima, Peru

Abstract: Abstract. Severe Plasmodium falciparum malaria is uncommon in South America. Lima, Peru, while not endemic for malaria, is home to specialized centers for infectious diseases that admit and manage patients with severe malaria (SM), all of whom contracted infection during travel. This retrospective study describes severe travel-related malaria in individuals admitted to one tertiary care referral hospital in Lima, Peru; severity was classified based on criteria published by the World Health Organization in 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The association between longer time losses in a malaria patient and delayed malaria diagnosis could reflect a more compromised clinical case (without the need for hospitalization) that requires more recovery time. Indeed, several studies have shown an increase in malaria severity with a delay in malaria case management [20,46,47], thus the WHO's recommendation of insuring access to early diagnosis, and prompt, effective treatment within 24-48 h of the onset of malaria symptoms [30]. The reduced group of participants (37.1%) with malaria diagnosis within 48 h of onset of symptoms suggests that the delay in the malaria diagnosis remains a pitfall of the malaria case management in the rural and widely dispersed population of the Peruvian Amazon, as previously found by a longitudinal study (2001)(2002)(2003) in riverine and road-associated rural populations of peri-Iquitos districts [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The association between longer time losses in a malaria patient and delayed malaria diagnosis could reflect a more compromised clinical case (without the need for hospitalization) that requires more recovery time. Indeed, several studies have shown an increase in malaria severity with a delay in malaria case management [20,46,47], thus the WHO's recommendation of insuring access to early diagnosis, and prompt, effective treatment within 24-48 h of the onset of malaria symptoms [30]. The reduced group of participants (37.1%) with malaria diagnosis within 48 h of onset of symptoms suggests that the delay in the malaria diagnosis remains a pitfall of the malaria case management in the rural and widely dispersed population of the Peruvian Amazon, as previously found by a longitudinal study (2001)(2002)(2003) in riverine and road-associated rural populations of peri-Iquitos districts [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Severe vivax malaria in Peru appears to have similar characteristics compared with elsewhere in Amazonia,59 but appears to be less common in Amazonia than in India 60. In the Loreto region, more than two-thirds of cases of severe malaria arriving at referral hospitals are due to P. vivax and belong to Group I of the new WHO classification, meaning that, because of the possibility of P. falciparum coinfection (without parasitological proof),61 such cases must be treated with intravenous AS in addition to standard P. vivax therapy. Although such cases present with profound prostration, the level of consciousness is generally preserved.…”
Section: Plasmodium Vivax Malaria In Perumentioning
confidence: 96%